Varying Response of the Concentration and Yield of Soybean Seed Mineral Elements, Carbohydrates, Organic Acids, Amino Acids, Protein, and Oil to Phosphorus Starvation and CO2 Enrichment - Singh, Shardendu K.; Barnaby, Jinyoung Y.; Reddy, Vangimalla R.; Sicher, Richard C. (Frontiers in Plant Science, 2016)
A detailed investigation of the concentration (e.g. mg g-1 seed) and total yield (e.g. g plant-1) of seed mineral elements and metabolic profile under phosphorus (P) starvation at ambient (aCO2) and elevated carbon dioxide (eCO2) in soybean is limited. Soybean plants were grown in a controlled environment at either sufficient (0.50 mM P, control) or deficient (0.10 and 0.01 mM, P-stress) levels of P under aCO2 and eCO2 (400 and 800 µmol mol-1, respectively). Both the concentration and yield of 36 out of 38 seed components responded to P treatment and on average 25 and 11 components increased and decreased, respectively, in response to P starvation. Concentrations of carbohydrates (e.g. glucose, sugar alcohols), organic acids (e.g. succinate, glycerate) and amino acids increased while oil, and several minerals declined under P deficiency. However, the yield of the majority of seed components declined except several amino acids (e.g. phenylalanine, serine) under P deficiency. The concentration-based relationship between seed protein and oil was negative (r2 = 0.96), whereas yield-based relationship was positive (r2 = 0.99) across treatments. The CO2 treatment also altered the concentration of 28 out of 38 seed components, of which 23 showed decreasing (e.g. sucrose, glucose, citrate, aconitate, several minerals and amino acids) while C, iron, Mn, glycerate and oil showed increasing trends at eCO2. Despite a decreased concentration, yields of the majority of seed components were increased in response to eCO2, which was attributable to the increased seed production especially near sufficient P nutrition. The P × CO2 interactions for the concentration of amino acids and the yield of several components were due to the lack of their response to eCO2 under control or the severe P starvation, respectively. Thus, P deficiency primarily reduced the concentration of oil and mineral elements but enhanced a majority of other components. However, seed components yield consistently declined under P starvation except for several amino acids. The study highlighted a P nutritional-status dependent response of soybean seed components to eCO2 suggesting the requirement of an adequate P supply to obtain the beneficial effects of eCO2 on the overall yield of various seed components.